Growth and Fixed Language Mindsets in Indonesian Migrant Workers (PMI) from West Kalimantan - Oktavianda, Melti; Lubis, Laila Nurfitrah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The hashtag